2020
DOI: 10.7554/elife.60861
|View full text |Cite
|
Sign up to set email alerts
|

Defining the function of OmpA in the Rcs stress response

Abstract: OmpA, a protein commonly found in the outer membrane of Gram-negative bacteria, has served as a paradigm for the study of b-barrel proteins for several decades. In Escherichia coli, OmpA was previously reported to form complexes with RcsF, a surface-exposed lipoprotein that triggers the Rcs stress response when damage occurs in the outer membrane and the peptidoglycan. How OmpA interacts with RcsF and whether this interaction allows RcsF to reach the surface has remained unclear. Here, we integrated in vivo an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 63 publications
4
32
0
Order By: Relevance
“…We have also obtained evidence that OmpA competes with BamA for an interaction with DolP. A role of OmpA in buffering the function of an envelope stress factor has been reported (Dekoninck et al, 2020). We propose that, during envelope stress, the depletion of OmpA might enhance the interaction of DolP with BamA.…”
Section: Discussionsupporting
confidence: 54%
“…We have also obtained evidence that OmpA competes with BamA for an interaction with DolP. A role of OmpA in buffering the function of an envelope stress factor has been reported (Dekoninck et al, 2020). We propose that, during envelope stress, the depletion of OmpA might enhance the interaction of DolP with BamA.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, OmpA was recently identified as a competitive binder of the lipoprotein RcsF ( 49 ), which we also identified as significantly upregulated during phage infection (FC +1.6). RcsF is a positive regulator of the Rcs stress response ( 50 ), of which we identified the significant upregulation of Rcs components RcsD (FC +1.7) during infection.…”
Section: Resultsmentioning
confidence: 64%
“…OmpA also seems to have a role in maintaining envelope integrity by linking the outer membrane to the peptidoglycan layer through the noncovalent linkage of its C-terminal domain to peptidoglycan ( 36 ). In addition to this activity, OmpA has a direct interaction with peptidoglycan stress sensory protein RcsF ( 49 ), which we also saw upregulated during infection (FC +1.6). Pal protein is also a mediator of outer membrane and peptidoglycan stability by forming a structural linkage between both layers ( 35 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A recent study showed that OmpA is unlikely the vehicle allowing RcsF to reach the surface ( Dekoninck et al, 2020 ). Components of the Bam machinery, which assemble and localize OMPs, are needed to localize RcsF within the OMPs ( Cho et al, 2014 ; Konovalova et al, 2014 , 2016 ; Dekoninck et al, 2020 ; Rodríguez-Alonso et al, 2020 ). Rodríguez-Alonso et al reported the crystal structure of the key BAM component BamA in complex with RcsF and revealed how BamA interacts with RcsF.…”
Section: An Overview Of the Rcs Systemmentioning
confidence: 99%